Pathogenetic links of the combined course of chronic pancreatitis and hypertensive disease and their role in the formation of complications - В'юн, Тетяна Іванівна; Viun, T.; Pasieshvili, L. (My University, 2018)
Pathogenetic links of the combined course of chronic pancreatitis and hypertensive disease and their role in the formation of complications
Keywords: pathogenetic links; combined course; chronic pancreatitis; hypertensive disease; role in the formation of complications